Emic-Epistemological Politeness in Digital Public Discourse: An Integrative Discursive Pragmatics Approach - R. Kunjana Rahardi; Agatha Umifriska Ariyani (Masyarakat Linguistik Indonesia, 2026)
This study examines emic–epistemological politeness in social media discourse from the perspective of integrative discursive pragmatics, drawing on politeness theory and epistemic pragmatics as its theoretical framework. It argues that politeness is not merely a strategy of interpersonal mitigation, but an epistemically grounded and reflexive resource for articulating social criticism within digital public spheres. The study explores how discursive practices are strategically employed to negotiate meaning, manage face relations, and construct epistemic legitimacy in response to socio-political issues. Employing a qualitative design within an interpretative–constructivist paradigm, the study utilizes critical discourse analysis. The data consist of selected social media utterances expressing social criticism, collected through non-participatory observation and systematic digital documentation. A purposive sampling technique was applied. The analysis is guided by an integrative discursive-pragmatic framework that incorporates situational, social, cultural, and cybertextual dimensions, with particular attention to multimodality and facework. Findings indicate that emic–epistemological politeness is realized through interconnected discursive strategies. Factual–persuasive constructions foreground moral accountability in public governance, while persuasive generalizations, often grounded in the epistemic authority of public figures, intensify critiques of political integrity. Reframing strategies destabilize dominant normative discourses by reconfiguring moral and socio-political relations. In addition, implicit delegitimization operates as an indirect yet effective critical resource, while contrastive strategies expose inequalities in social recognition, particularly in gendered responses to sensitive issues.